An advanced strategy for efficient recycling of bovine bone: Preparing high-valued bone powder via instant catapult steam-explosion. (16th April 2022) - Qin, Xiaojie; Shen, Qingshan; Guo, Yujie; Liu, Jiqian; Zhang, Hongru; Jia, Wei; Xu, Xiong; Zhang, Chunhui
Graphical abstract: Highlights: ICSE destructed bovine bone with protein and mineral dissolved. ICSE notably shortened BBP process time and lowered energy consumption. ICSE endowed BBP with more protein and essential minerals. ICSE greatly improved the mineral release and protein digestibility of BBP without cytotoxicity. The paper provided an effective way for reusing bovine bone as nutrition-fortified BBP. Abstract: As the major byproduct of meat processing, bovine bone are produced in large amounts annually. However, the inefficient utilization with low-added value resulted in serious resource waste. The study aims to prepare high-value bovine bone power (BBP) via instant catapult steam-explosion (ICSE) treatment, taking ball milling (BM) method as control. Results showed that ICSE treatment deconstructed bovine bone with more holes emerging, and effectively promoted mineral dissolution and protein degradation while reduced energy consumption. Compared with BM-BBP, ICSE-BBP possessed more protein and essential minerals, presenting in regular elliptical shapes with narrow distribution of particle size (0.1 ∼ 40 μm), and owned better solution stability and protein solubility. ICSE-BBP also exhibited higher mineral release and protein digestibility during GI digestion while revealed no obvious cytotoxicity, indicating the potential applicability in nutrition-fortified foods. Taken together, ICSE technology holds promise in reusing bovine bone, providing an efficient and eco-friendly process for BBP industrial production.